A cultural ecology of new public management in Indonesia / Ismi Rajiani and Isma Addi Jumbri - Rajiani, Ismi; Jumbri, Isma Addi (Universiti Teknologi MARA, Shah Alam, 2011)
In 1980s, new public management (NPM) gained popularity as a universal model of reform in public sector management. However, in South East Asia, there have been significant differences between countries that have been successful in NPM reform. Drawing on frameworks of national culture, this article is aimed at exploring the applicability of NPM in the developing country of Indonesia. Using Hofstede’s construct of national culture, social units in Indonesia are explained with NPM proposed as a culturally dependent strategy. It is suggested that the successful implementation of NPM requires compliance between the reform strategies that are adopted and the country’s cultural characteristics. Prior failure in the implementation of NPM has rekindled the interest in the “old” bureaucratic paradigm which was then an indispensable foundation in the field.